Construção de bioeletrodo para detecção da bactéria Neisseria meningitidis - Castro, Ana Cristina Honorato de (2012)
A novel DNA electrochemical biosensor to detection of bacterial meningitis, a worldwide endemic human disease, was investigated and is reported in this paper. This device is based in the use as molecular probe of specific DNA fragments of the genome of the bacteria Neisseria meningitidis, incorporated onto graphite electrode modified with poly(4-aminophenol). In this device, the presence of a complementary specific DNA sequence was evaluated monitoring the DNA hybridization reaction by differential pulse voltammetry, using an electroactive intercalator ethidium bromide as hybridization indicator. The proposed DNA biosensor showed that complementary oligonucleotide (NM2) could be quantified with a low detection limit (1.4 × 10 -10 mol.L-1, S/N=3) and good linearity (R=0.995). In addition, the biosensor showed high selectivity, discriminating non-specific targets and retaining more than 90% of its original activity, after 120 days of storage.